FURTHER EXPLORATION OF THE KLEE-MINTY PROBLEM - B. P. SILALAHI (MILANG Journal of Mathematics and Its Applications, 2010)
The Klee-Minty problem is explored in this paper. The coordinates formulas of all vertices of the Klee-Minty cube are presented. The subset representation of the vertices of the Klee-Minty cube is discussed. How to construct the Klee-Minty path is showed. It turns out that there are rich structures in the Klee-Minty path. We explore these structures. Key words: Klee-Minty cube, Klee-Minty path, Klee-Minty problem.